Description of chlorophyll a spatial distribution, temperature and salinity on the continental shelf and slope of the Central American Caribbean - Brenes-Rodríguez, Carlos Luis; Benavides-Morera, Rosario; Loza-Álvarez, Sandra (Revista Ciencias Marinas y Costeras, 2017)
Under the regional coordination of OSPESCA (Central America Fisheries and Aquaculture Organization), an exploratory fishing survey campaign on the continental shelf and slope of the Central American Caribbean was conducted from January 3rd to February 3rd, 2011 on board the Miguel Oliver R/V. Temperature and salinity were determined in 76 hydrographic stations, and chlorophyll a concentration was estimated using a CTD fluorometer. Surface temperature ranged between 25°C and 27°C and salinity at that same level was between 32.5 (Panama) and 35.5 (Belize). The thermocline depth showed a descending tendency from south to north between 140 and 155 m. Chlorophyll a concentration ranged between 0.01 and 1.01 mg m-3. The distribution of chlorophyll a in the 0 to 150 m layer was the highest in Panama (25.25 mg m-2) and the lowest in Belize (6.05 mg m-2). Two chlorophyll a maximums (mixing layer and thermocline layer) characterize the southern area of the Central American Caribbean (Costa Rica and Panama), while only one maximum close to 90 m stands out in the vertical distribution of that variable between Nicaragua and Belize. Average chlorophyll a concentration for all stations was 0.3 mg m-3; therefore, in general oligotrophic conditions stand out in the continental shelf and slope.